The relationship between language, thinking and culture - Ilona Lekhner; Лехнер Ілона; Lechner Ilona (Науково-дослідний центр інноваційних технологій, 2020)
Abstract. In the course of my research, I review the main principles of cognitive semantics on the basis of the English and Hungarian scientific literature. The aim of the research is therefore to define the central concepts and to shed light on the connections between language, thinking and culture.
Keywords: cognition; conceptualisation; cognitiv linguistics